The elderly population’s social networks and HIV perceptions: Evidence from China - Jie Shen; Junfang Xu (Journal of Family Medicine and Primary Care)
Background: Previous studies have found that people with low participation in social activities and living alone were prone to have risky sexual behaviors, while people with high participation in social activities were less prone to have risky sexual behaviors. Based on the above assumptions, we conducted an analysis on elderly population’s social networks and human immunodeficiency virus (HIV) risky behaviors in China. In the survey study, considering the sensitivity of sexual behavior, HIV risk behavior of the elderly population is more difficult to measure, so the intermediate variable of HIV perceptions was used instead of the sexual behavioral variable. Methods: A cross-sectional study was conducted in July to September 2023 among the elderly aged ≥ 50 years in China to measure the social networks with the Social Support Rate Scale (SSRS) and to measure the HIV perceptions of the elderly with the degree of knowledge of acquired immunodeficiency syndrome (AIDS) prevention and treatment and the degree of discrimination of HIV/AIDS patients, and the data were statistically analyzed with SPSS 27.0 software. Statistical analysis methods included descriptive analyses such as frequency, percentage, mean ± standard deviation, and median, two independent samples t-test analysis, and multivariate logistic regression model analysis. Results: Among the 1022 elderly people surveyed, the proportion of those with weak and strong levels of social support was 46.9% and 53.1%, respectively; the proportion of those with low, medium, and high levels of HIV knowledge perceptions was 4.8%, 5.9%, and 89.3%, respectively; and the proportion of those with low, medium, and high levels of attitudinal perceptions was 24.7%, 35.0%, and 40.3%, respectively. Based on the Goodman–Kruskal Gamma test, it was found that there was a positive correlation between social support and HIV knowledge perceptions in the elderly population, and there was a negative correlation between social support and HIV attitudinal perceptions in the elderly population. Ethnicity, current occupation or pre-retirement occupation, personal average after-tax monthly income, attitudinal perceptions, and social support were the influencing factors for the knowledge perceptions in the elderly population (P < 0.05); literacy, number of children, mode of residence, personal average monthly income after tax, knowledge perceptions, and social support were the influencing factors of attitudinal perceptions in the elderly population (P < 0.05). Conclusions: There is a correlation between social networks and HIV perceptions in China’s elderly population, which is positively correlated with HIV knowledge perceptions and negatively correlated with HIV attitudinal perceptions, and it is important to improve the HIV prevention and knowledge of the elderly population and reduce their HIV-related discrimination.